Boracene-based alkylborate enabled Ni/Ir hybrid catalysis. Issue 34 (19th August 2020) - Sato, Yukiya; Miyamoto, Yusuke; Sumida, Yuto; Hosoya, Takamitsu; Ohmiya, Hirohisa
Abstract : Boracene-based alkylborate enabled visible light-mediated Ni/Ir metallaphotoredox catalysis. Abstract : Boracene-based alkylborate enabled visible light-mediated metallaphotoredox catalysis. The directly excited borate was easily oxidatively quenched by an excited Ir photoredox catalyst. Ni/Ir hybrid catalysis afforded the products under significantly low irradiance.